Efektivitas media kartu aksara menggunakan metode small group discussion terhadap keterampilan menulis aksara jawa kelas v gugus 2 Ahmad Yani - Pradesiwi, Annisa Rahma; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2025)
This research was conducted to determine the effectiveness of using the Small Group Discussion method using card learning media in improving Javanese script writing skills in class V Cluster 2 Ahmad Yani. This research is an experiment using a Quasi Experimental Nonequivalent Control Group design involving an experimental group and a control group. Data collection methods used include interviews, observation, documentation, and tests. The validity test is carried out using tests that refer to indicators, and instruments that have been validated by experts will be tested in the instrument trial group. Data analysis was performed using parametric statistical tests T-test with independent sample t-test to compare the averages of two unpaired samples. The results showed that the use of card learning media using the Small Group Discussion method was effective in improving the writing skills of Javanese script in class V Cluster 2 Ahmad Yani. It is proven that the use of cards as a shared learning medium with the Small Group Discussion method resulted in an increase of 1.29% in the experimental group, while the control group using conventional methods experienced an increase of 1.18%. Based on this explanation, it can be concluded that the use of card learning media with the Small Group Discussion method is effective in improving the writing skills of Javanese script in class V Cluster 2 Ahmad Yani students.